Conservation genetics of the bonnethead shark Sphyrna tiburo in Bocas del Toro, Panamá : preliminary evidence of a unique stock ; Population genetics of the endangered hammerhead sharks Sphyrna mokarran and Sphyrna lewini of South Florida, USA (2017)
"Ch1. The bonnethead shark, Sphyrna tiburo, is a small elasmobranch predator distributed along the Western Atlantic, including the Caribbean. Population structure and genetic diversity of this highly philopatric and non-dispersive species, was assessed in Bocas del Toro Archipelago, Panama. Two mitochondrial fragments of the genes cytochrome oxidase I (COI) and control region (CR) were used to test the genetic structure of adult and juvenile S. tiburo in this area, in comparison with other locations of the Western Atlantic. Our analyses found significant genetic differentiation between Caribbean bonnethead sharks from Bocas del Toro, and other bonnetheads from other locations of the Western Atlantic and Belize. These results suggests that Bocas del Toro, could constitute a different genetic population unit for this species, thus, bonnethead sharks in this area could belong to a unique stock. Ch2. The great hammerhead shark Sphyrna mokarran and the scalloped hammerhead shark Sphyrna lewini, are two highly threatened species, affected by commercial..."--Tomado del Formato de Documento de Grado.